Customer Satisfaction in Private Banking - Volker Seiler; Markus Rudolf (Credit and Capital Markets – Kredit und Kapital, 2014)
The paper at hand presents a customer satisfaction model for the private banking industry. We empirically assess the postulated model with the help of partial least squares (PLS) and use formative measurement models for the predictors of customer satisfaction and customer loyalty. The results of the structural model show good quality of the overall model. Customer satisfaction in the private banking industry is mainly determined by service value and the relationship manager. In addition, the relationship manager is an essential predictor of customer loyalty and relationship quality. – – Kundenzufriedenheit im Private Banking Die vorliegende Arbeit postuliert ein Modell zur Kundenzufriedenheit im Private Banking. Im Rahmen der empirischen Studie wird das Modell mit Hilfe von Partial Least Squares (PLS) geschätzt. Methodisch begeht die Arbeit insofern Neuland, als dass die Treiber der Kundenzufriedenheit und -bindung als formative Konstrukte modelliert werden. Die Ergebnisse der Analyse des Strukturmodells zeigen eine gute Gesamtmodellgüte. Hinsichtlich der Determinanten der Kundenzufriedenheit fällt auf, dass diese im Wesentlichen durch das Preis-Leistungs-Verhältnis sowie den Berater determiniert wird. Auch für die Kundenbindung und Beziehungsqualität kommt den Beratern im Private Banking eine entscheidende Bedeutung zu.
Keywords: G21; M31; C3; 330; Private Banking; Private Wealth Management; Customer Satisfaction; Partial Least Squares